Breast Hemangioma: MR Appearance with Histopathological Correlation - Ameen, Rasha (Medknow Publications & Media Pvt Ltd, 2012)
Breast hemangioma is a rare tumor and when small, it may be difficult to diagnose using conventional imaging techniques. In this report the MR appearance is described with histopathological correlation.